Magicians of Light : Photographs from the Collection of the National Gallery of Canada. - Borcoman, James; McElbone, John P.; Thomson, Shirley L. (Ottawa : National Gallery of Canada, 1993)
Fox Talbot, William Henry ; Eynard-Lullin, Jean-Gabriel ; Hill, David Octavius ; Adamson, Robert ; Biewend, Hermann Carl Edgard ; Caneva, Giacomo ; Moulin, Félix Jacques A. ; Owen, Hugh ; Negre, Charles ; Camp, Maxime Du ; Marville, Charles ; Blondel, A. Le ; Teynard, Félix ; Baldus, Edouard ; Babbitt, Platt D. ; Turner, Benjamin Brecknell ; Méhédin, Léon-Eugène ; Delamotte, Philip Henry ; Cundall, Joseph ; Barnard, George N. ; Salzmann, Auguste ; Fenton, Roger ; Greene, John Beasly ; Gray, Gustave Le ; Frith, Francis ; Hime, Humphrey Lloyd ; England, William ; Notman, William ; Beato, Felice ; Macpherson, Robert ; Ellisson, George William ; Henderson, Alexander ; Carjat, Etienne ; Ponti, Carlo ; Bourne, Samuel ; Knox, David ; Gardner, Alexander ; Skeen and Co., W.L.H. ; Annan, Thomas ; Andrieu, Jules ; Cameron, Julia Margaret ; Weed, Charles Leander ; O'Sullivan, Timothy H. ; Burki, John ; Bell, William ; Muybridge, Eadweard ; Thomson, John ; Emerson, Peter Henry ; Kühn, Heinrich ; Boughton, Alice M. ; Haviland, Paul B. ; Käsebier, Gertrude ; Langdon Coburn, Alvin ; Steichen, Edward ; Atget, Eugène ; Evans, Frederick H. ; Stieglitz, Alfred ; Strand, Paul ; Weston, Edward ; Watkins, Margaret ; Man Ray ; Outerbridge, Paul ; Sudek, Josef ; Rudomine, Alfred ; Kertesz, André ; Funke, Jaromir ; Bruehl, Anton ; Moholy, Lucia ; Rodchenko, Alexander ; Sander, August ; Renger-Patzsch, Albert ; Rayer, Herbert ; Ignatovich, Boris ; Hine, Lewis Wickes ; Steiner, Ralph ; Kesting, Edmund ; Hajek-Halke, Heinz ; Brassaï ; Cartier-Bresson, Henri ; Heartfield, John ; Abbott, Berenice ; Evans, Walker ; Engel, Morris ; Sommer, Frederick ; Adams, Ansel ; Weegee ; Beaton, Cecil ; Model, Lisette ; Tabard, Maurice ; Grossman, Sid ; White, Minor ; Mariën, Marcel ; Levinstein, Leon ; etc.
biografie
Magicians of Light : Photographs from the Collection of the National Gallery of Canada, The National Gallery of Canada, Ottawa, 4 June to 6 September 1993
Engels
boek
Keywords: Canada